Benefits of exercise and/or physical activity in the five types of cancer with the highest incidence and mortality worldwide: A narrative review - Fuentes-Nuñez, Javier; Olivares-Gómez, Carelia; Farías-Valenzuela, Claudio; Poblete-Aro, Carlos; Alvarez-Arangua, Sebastián; Ferrero-Hernández, Paloma (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
This review aims to declare the benefits of physical exercise and/or physical activity in the five types of cancer with the highest mortality rate in the world. A search was carried out in the databases: Pubmed, Cochrane, Scopus, Web of science, Scielo (Latin America) and Medline. The terms used for the search were: “lung cancer,” “liver cancer,” “breast cancer,” “stomach cancer,” “colon cancer,” “physical exercise,” “physical activity,” “exercise.” resistance” and “aerobic exercise”. Physical exercise and physical activity have shown benefits in morphological, metabolic and psychological variables, having a positive impact on increasing functionality, life expectancy and quality of life in cancer patients. Aerobic exercise demonstrated greater benefits in oxygen consumption, in addition to high adherence, while strength training in greater capacity specifically in the lower limbs.